CVD growth of molybdenum diselenide surface structures with tailored morphology. Issue 33 (2nd August 2018) - Sial, M. Naeem; Usman, Muhammad; Zheng, Binjie; Yu, Yanan; Mavrič, Andraž; Qing, Fangzhu; Valant, Matjaz; Wang, Zhiming M.
Abstract : Controllable atmospheric pressure CVD has been optimized to grow transition metal dichalcogenide MoSe2 with tunable morphology at 750 °C on a silicon substrate with a native oxide layer of 250 nm. Abstract : Controllable atmospheric pressure CVD has been optimized to grow transition metal dichalcogenide MoSe2 with tunable morphology at 750 °C on a silicon substrate with a native oxide layer of 250 nm. Utilizing tetrapotassium perylene-3, 4, 9, 10-tetracarboxylate (PTAS) as a seed promoter and varying the vertical distance between the substrate and the precursor MoO3, different morphologies of MoSe2 were achieved, including 2D triangles, hexagons, 3D pyramids and vertically aligned MoSe2 sheets. We find that the shape of MoSe2 is highly dependent upon the distance h between the substrate and the precursor. The change in the morphology is attributed to the confinement of vapor (MoO3 and Se) precursors and their concentrations due to the change in h . These results are helpful in improving our understanding about the factors which influence the morphology (shape evolution) and also the continuous growth of MoSe2 films.